Evidence for melting of HD and D-2 clusters in solid neon below 1 K - Sheludiakov S; Ahokas J; Jarvinen J; Lehtonen L; Vasiliev S; Dmitriev YA; Lee DM; Khmelenko VV (AMER PHYSICAL SOC, 2022)
We report on an electron spin resonance study of H and D atoms stabilized in solid mixtures of neon, molecular deuterium, and hydrogen deuteride. We observed that H and D atoms can be stabilized in pure HD and D-2 clusters formed in pores of solid Ne as well as in a Ne environment. Raising temperature from 0.1 to 1.3 K results in a rapid recombination of a significant fraction of both H and D atoms in HD and D-2 clusters. The recombination rate appears to be five and seven orders of magnitude faster than in solid bulk samples of HD and D-2, respectively. We explain this recombination rate enhancement by melting of clusters of molecular hydrogen isotopes, similar to what has been observed for atomic hydrogen in H-2 clusters [Sheludiakov et al., Phys. Rev. B 97, 104108 (2018)]. Our observations do not provide evidence for a superfluid behavior of these clusters at temperatures of 0.1-1.3 K.